Assessment of the preferences of red swamp crayfish (Procambarus clarkii) fed with Riparian tree leaves: A microcosm study. Issue 4 (5th August 2013) - Fidalgo, Maria Leonor; Ferreira, Cláudia; Sampaio, Ana
Abstract We conducted a microcosm study to assess the preferences of Procambarus clarkii (Girard, 1852), an invasive and successful crayfish species, for conditioned leaf litter from alder, oak, and plane with and without feces access. Some chemical foliar characteristics were determined at the beginning and at the end of the experiment. Alder and plane leaves had higher total nitrogen and lower C:N ratio than oak. Oak and plane exhibited similar polyphenol contents. Animals preferred alder>plane>oak leaves (p < 0.0001) and a coprophagous trend was observed. Consumption rates varied among litters according to fecal availability and the interaction litter/fecal availability. Our results suggest that the importance of P. clarkii in breakdown of riparian tree leaves depends not only on the tree species and their characteristics, but also on access to fecal material. Leaf species with high N contents and low C:N ratios would be preferably consumed by the crayfish, and the consumption would be faster in lotic than in lentic systems.